2018
DOI: 10.1038/hgv.2018.8
|View full text |Cite
|
Sign up to set email alerts
|

iMETHYL: an integrative database of human DNA methylation, gene expression, and genomic variation

Abstract: We launched an integrative multi-omics database, iMETHYL (http://imethyl.iwate-megabank.org). iMETHYL provides whole-DNA methylation (~24 million autosomal CpG sites), whole-genome (~9 million single-nucleotide variants), and whole-transcriptome (>14 000 genes) data for CD4+ T-lymphocytes, monocytes, and neutrophils collected from approximately 100 subjects. These data were obtained from whole-genome bisulfite sequencing, whole-genome sequencing, and whole-transcriptome sequencing, making iMETHYL a comprehensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
59
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(62 citation statements)
references
References 13 publications
3
59
0
Order By: Relevance
“…For example, the iMethyl database (http://imethyl.iwate-megabank. org) [56,57] of methylation sites and regulatory effects in peripheral blood mononuclear cells (PBMCs) indicates that this locus is regulatory for the adjacent gene LAMB3 in CD4T cells (effect = 0.0091, p = 4.55 × 10 -5 ). However, both LAMB3 and G0S2 were upregulated in an amyloid β peptide stimulation study of microglia, which suggests that they could be co-regulated [58].…”
Section: Discussionmentioning
confidence: 99%
“…For example, the iMethyl database (http://imethyl.iwate-megabank. org) [56,57] of methylation sites and regulatory effects in peripheral blood mononuclear cells (PBMCs) indicates that this locus is regulatory for the adjacent gene LAMB3 in CD4T cells (effect = 0.0091, p = 4.55 × 10 -5 ). However, both LAMB3 and G0S2 were upregulated in an amyloid β peptide stimulation study of microglia, which suggests that they could be co-regulated [58].…”
Section: Discussionmentioning
confidence: 99%
“…S7 ). Expression quantitative trait locus (eQTL) analysis using Japanese multi-omics iMETHYL datasets 25 , 32 , 33 showed that the rs8022678 A allele was weakly associated with decreased BCL11B expression level in CD4 + T cells (Supplementary Fig. S8 ).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies indicated that the 3′- BCL11B gene desert region harbours several remote enhancers that modulate BCL11B gene expression 34 , 35 . Japanese multi-omics iMETHYL datasets 25 , 32 , 33 showed that the rs8022678 A allele was weakly associated with decreased BCL11B expression level in CD4 + T cells. Some variants at the 3′- BCL11B gene desert region were associated with aortic stiffness and cardiovascular disease risk 36 , although rs8022678 was not linked with those variants by linkage disequilibrium ( r 2 = 0.002 in East Asians according to the LDlink server 37 ).…”
Section: Discussionmentioning
confidence: 99%
“…iMETHYL is an integrative database of human DNA methylation, gene expression, and genomic variation data. It provides cell-type-specific browser tracks (e.g., CD4T, monocytes, and neutrophils) for examining DNA methylation variation, gene expression and single-nucleotide variants in any region of the human genome [25]. These tools are convenient because they provide an interface for representing the results of integrative analyses of methylation and expression data directly from databases.…”
Section: Feature Comparison With Other Bioinformatic Softwarementioning
confidence: 99%
“…ViewBS can correlate between non-CG methylation and gene expression, but the users need to process the data first to allow correlation analyses. MethHC [24] and iMETHYL [25] are databases of methylation and gene expression. They do not allow users to provide their own data, and they can only be applied to specific species.…”
Section: Introductionmentioning
confidence: 99%